Dampak Tempat Pembuangan Akhir Sampah (TPA) Terhadap Gangguan Kesehatan Masyarakat - Astry Axmalia; Surahma Asti Mulasari (Jurnal Kesehatan Komunitas, 2020)
The presence of a garbage disposal in a region will certainly cause problems for the surrounding population, especially those settling with a distance of < 1 km. Based on government regulation No 18 year 2012 that the distance of settlement should be more than 1 km. If landfills are not managed properly, will certainly cause pollution of water quality, air pollution, soil pollution from piles of garbage piled up. This literature study aims to determine the health impact of communities living around landfill waste and risk factors that can increase health disorders of the community. The method used in this study is literature review. The collection of literature is conducted through http://garuda.ristekdikti.go.id and Google Scholar databases published in the period from 2015 to 2019. Health complaints found in the community around the TPA are skin diseases, diarrhea, respiratory disorders, chest pains, sore eyes, dry throat, hot throat, dizziness, coughs, worms and shortness of breath. There are factors that also cause public health disorders around TPA are environmental factors such as poor air quality that is affected by water pollution, air pollution, soil pollution that can cause disease arise due to the buildup and accumulation of garbage that causes the breeding of bacteria, vector diseases and viruses. Keywords: Landfill, Health Problems